An extended ultrasonic time-of-flight method for measuring lubricant film thickness. (July 2015) - Geng, Tao; Meng, Qingfeng; Xu, Xinping; Wang, Peigong; Yuan, Xiaoyang
An extended ultrasonic time-of-flight (TOF) method is proposed for measuring the thickness of lubricant film. Based on the spectrum analysis method of superimposed pulses, the extended TOF determines the travel time of ultrasonic wave and subsequently the film thickness in frequency domain. The method extends the measurable range of the original TOF method to the lubricant films of superimposed reflected pulses, which usually processed by the resonance model. The extended TOF gives another interpretation to the resonance phenomenon described by the resonance model. In theory and practice, the extended TOF integrates the resonance model and the original TOF method into one approach. This solved the problem that film thickness monitoring program needs to alter between time and frequency domains according to the changing of film thickness. A precision experimental apparatus was designed for verifying the correctness of the method. The lubricant films of different thickness were measured repeatedly and the measuring accuracy was analyzed.